Throughout the developing world, working animals are still vital important power bases of the small farmers' systems of production and transportation. With economic development, there is a growing interest in the animals for pleasure purposes, not only for aesthetic value but also for sport requiring speed and stamina for racing and other physical performances. An understanding of the physiology of exercise of animals is therefore needed including practical application such as to evaluate c - Djokowoerjo Sastradipradja; I Ketut Sumadi; I Gede Mahardika (Media Veteriner, 1999)
Throughout the developing world, working animals are still vital important power bases of the small farmers' systems of production and transportation. With economic development, there is a growing interest in the animals for pleasure purposes, not only for aesthetic value but also for sport requiring speed and stamina for racing and other physical performances. An understanding of the physiology of exercise of animals is therefore needed including practical application such as to evaluate cardiorespiratory fitness and information on training for improvement in health related fitness and performance. Under the existing local condition, success have been reached to record heart rate of animals telemetrically over extended periods, and to measure longterm body energy expenditures of large animals (buffalo) involving energy balance approaches and ill vivo body composition measurements by the water displacement method. These measurements enable the development of a modest practical fitness guideline for exercising swamp/ water buffalo, e.g. V02 = (0.1 X + 3.4) ml/min/kg BW for walking, and V02 =(0.2 X + 3.4) ml/min/kg BW for trot at 100-250 m/min speed. This value at a given speed offers a measure of running economy. The value of the oxygen pulse as an index of fitness is presented, above 0.05 is regarded athletic, while lower than 0.05 is the opposite. For the female buffalo the value is 0.066 at rest but decreases with exercise of pulling a load due to moving the body with a slower speed. Male buffalo has a higher oxygen pulse, 0.094 at rest and increases with exercise. Training seems to improve the oxygen pulse. These data enable the calculation of the heart's stroke volume and the O2 debt, which are other parameters of fitness. The field of exercise physiology of athletic animals in Indonesia should be explored. The acquisition of a treadmill, blood gas analysis and ergocardiorespirometry equipment for large athletic animals would be an advantage.